Faktor-Faktor Yang Berhubungan dengan Kurang Energi Kronik (KEK) pada Ibu Hamil di UPTD Puskesmas Cibugel - Yeti, Yeti; Nunung Nurjanah; Diani Magasida (Stikes Kesdam IV/Diponegoro Semarang, Indonesia, 2023)
Background: Based on data from the World Health Organization for 2021, it is stated that the number of maternal deaths in the world reaches 830 people every day caused by complications of pregnancy or childbirth and most maternal deaths occur in developing countries including Indonesia. AKI in Indonesia in 2021 will reach 830 people. At the UPTD Puskesmas Cibugel, it was recorded that the number of pregnant women with CED in 2022 was 47 out of 359 people with a percentage of 13.2%. Objective: to determine the factors associated with Chronic Energy Deficiency (CED) in Pregnant Women at the UPTD Health Center Cibugel, Sumedang Regency in 2023. Design: quantitative study using a cross-sectional survey approach. The study population was 32 pregnant women in the working area of the UPTD Puskesmas Cibugel in the period April - May 2023. The sample technique used total sampling. Results: there is a relationship between health conditions (nutrition status) and KEK in pregnant women. There is a relationship between age and CED in pregnant women and there is no relationship between parity and CED in pregnant women. Conclusion: factors associated with the incidence of CED include nutritional status and age. Meanwhile, parity has no relationship with the occurrence of KEK. It is recommended to increase cooperation in efforts to prevent and reduce KEK in pregnant women through cross-programs and cross-sectors.